(untitled) (Innovate Conferences, 2025)
This study explores the structural-semantic features of the "step" concept in English, analyzing its linguistic representation and cognitive significance. The research examines the morphological structure, syntactic functions, and semantic variations of the word "step" in different contexts. By utilizing a linguopragmatic approach, we highlight how the concept is used metaphorically and idiomatically in various discourse types. The findings contribute to a deeper understanding of conceptual categorization in language and its role in communication.